Enhanced H3K4me3 modifications are involved in the transactivation of DNA damage responsive genes in workers exposed to low-level benzene. (March 2018) - Li, Jie; Xing, Xiumei; Zhang, Xinjie; Liang, Boxuan; He, Zhini; Gao, Chen; Wang, Shan; Wang, Fangping; Zhang, Haiyan; Zeng, Shan; Fan, Junling; Chen, Liping; et al.
Abstract: In this study, we explore whether altered global histone modifications respond to low-level benzene exposure as well as their association with the hematotoxicity. We recruited 147 low-level benzene-exposed workers and 122 control workers from a petrochemical factory in Maoming City, Guangdong Province, China. The internal exposure marker level, urinary S-phenylmercapturic acid (SPMA), in benzene-exposed workers was 1.81-fold higher than that of the controls ( P  < 0.001). ELISA method was established to examine the specific histone modifications in human peripheral blood lymphocytes (PBLCs) of workers. A decrease in the counts of white blood cells (WBC), neutrophils, lymphocytes, and monocytes appeared in the benzene-exposed group (all P  < 0.05) compared to the control group. Global trimethylated histone 3 lysine 4 (H3K4me3) modification was enhanced in the benzene-exposed group ( P  < 0.05) and was positively associated with the concentration of urinary SPMA (β = 0.103, P  = 0.045) and the extent of DNA damage (% Tail DNA: β = 0.181, P  = 0.022), but was negatively associated with the leukocyte count (WBC: β = −0.038, P  = 0.023). The in vitro study revealed that H3K4me3 mark was enriched in the promoters of several DNA damage responsive (DDR) genes including CRY1, ERCC2, and TP53 in primary human lymphocytes treated with hydroquinone. Particularly, H3K4me3 modification was positively correlated with the expression of CRY1 in the PBLCs of benzene-exposed workers. These observations indicate that H3K4me3 modification might mediate the transcriptional regulation of DDR genes in response to low-dose benzene exposure. Graphical abstract: Highlights: Low dose benzene exposure leads to a decline of WBC counts. H3K4me3 modification was enhanced upon low dose benzene exposure in vitro and in vivo. H3K4me3 modification might mediate DNA damage response through transactivation of DDR genes. Abstract : H3K4me3 modification responds to low-level benzene exposure by regulating the expression of DNA damage responsive genes.